Necroptosis in Pulmonary Diseases: A New Therapeutic Target - Wang, Lingling; Zhou, Ling; Zhou, Yuhao; Liu, Lu; Jiang, Weiling; Zhang, Huojun; Liu, Huiguo (Frontiers in Pharmacology, 2021)
In the past decades, apoptosis has been the most well-studied regulated cell death (RCD) that has essential functions in tissue homeostasis throughout life. However, a novel form of RCD called necroptosis, which requires receptor-interacting protein kinase-3 (RIPK3) and mixed-lineage kinase domain-like pseudokinase (MLKL), receives growing research attention. The RIP homotypic interaction motif (RHIM)-dependent activation of RIPK3 enables the recruitment and phosphorylation of MLKL, which oligomerizes and translocates to the plasma membranes, leading to plasma membrane rupture and cell death. While apoptosis elicits no inflammatory responses, necroptosis triggers inflammation or causes an innate immune response to protect the body through the release of damage-associated molecular patterns (DAMPs). Therefore, evidence suggesting that necroptosis is implicated in the pathogenesis of several human diseases, such as systemic inflammation, respiratory diseases, cardiovascular diseases, neurodegenerative diseases, neurological diseases, and cancer, is increasing. This review summarizes the emerging insights of necroptosis and its contribution to the pathogenesis of lung diseases.